Trying to be Someone Else - Sharma, Rajaram (Voices of Teachers and Teacher Educators, 2017)
Teachers today are under a lot of pressure to perform. More critical, though, is to persuade everyone that she is performing. It seems that almost everyone outside of the classroom is an expert and is eager to advise the teacher on how to carry out her duties. To be fair to all of those uninvited advisors, they are valid participants in children’s education. They might be members of the greater community where we all live or parents of our pupils. As educators, we carry out our duties on behalf of this community, and education is a socialization process.